Bridget Jones : the edge of reason [videorecording (DVD)] - Kidron, Beeban; Zellweger, Renée, 1969-; Grant, Hugh; Firth, Colin, 1960-; Fielding, Helen, 1958- (Universal, 2005)
Not that Bridget is counting, but it's been six wonderful weeks, four fabulous days, and seven precious hours with one flawless boyfriend, Mark. But when mischievous and devilishly charming Daniel arrives on the scene claiming to be a reformed man, can Bridget find a way to make true love last forever?